Effects of Upper-Limb Exoskeletons Designed for Use in the Working Environment—A Literature Review - Moeller, Tobias; Krell-Roesch, Janina; Woll, Alexander; Stein, Thorsten (Frontiers in Robotics and AI, 2022)
Introduction: Many employees report high physical strain from overhead work and resulting musculoskeletal disorders. The consequences of these conditions extend far beyond everyday working life and can severely limit the quality of life of those affected. One solution to this problem may be the use of upper-limb exoskeletons, which are supposed to relieve the shoulder joint in particular. The aim of this literature review was to provide an overview of the use and efficacy of exoskeletons for upper extremities in the working environment. Methods: A literature review was conducted using the PICO scheme and the PRISMA statement. To this end, a systematic search was performed in the PubMed, Web of Science and Scopus databases in May 2020 and updated in June 2021. The obtained studies were screened using previously defined inclusion and exclusion criteria and assessed for quality. Pertinent data were then extracted from the publications and analysed with regard to type of exoskeleton used as well as efficacy of exoskeleton use. Results: 29 suitable studies were included in the review. 18 different exoskeletons were examined. The majority of the exoskeletons only supported the shoulder joint and were used to assist individuals working at or above shoulder level. The main focus of the studies was the reduction of muscle activity in the shoulder area. Indeed, 16 studies showed a reduced activity in the deltoid and trapezius muscles after exoskeleton use. Kinematically, a deviation of the movement behaviour could be determined in some models. In addition, study participants reported perceived reduction in exertion and discomfort. Discussion: Exoskeletons for upper extremities may generate significant relief for the intended tasks, but the effects in the field (i.e. working environment) are less pronounced than in the laboratory setting. This may be due to the fact that not only overhead tasks but also secondary tasks have to be performed in the field. In addition, currently available exoskeletons do not seem to be suitable for all overhead workplaces and should always be assessed in the human-workplace context. Further studies in various settings are required that should also include more females and older people.